Structure methods of compensation of communication lines influence by current in active resistance simulators - Bojko, Oksana; Hotra, Oleksandra; Stolyarchuk, Petro (Видавництво Національного університету «Львівська політехніка», 2002)
The structure methods of compensation of communication lines influence by current in four-wire active resistance simulators with transmission functions Rsim=R0μ, Rsim=R0(1-μ) are considered.
Keywords: four-wire active resistance simulator; compensation of communication lines influence